Multi Criteria Decision Making applied to Image Fusion – Limitations - C.Nalini, M. Shanmuganathan (International Journal of Advanced Science and Technology, 2020)
This paper elucidates the assessment of the Analytical Hierarchy Process (AHP), one of the Multi Criteria Decision Making (MCDM) routines, which was initiated by Saaty in the year 1980. It elucidates how the theories, concepts, and ideas of AHP are derived in certain types of situations, how it helps one in prudent decision-making, how an individual is able to understand the basic concepts of AHP, how the data are evaluated, how far it is effective in making recommendations for expounding complex problems, and what are the benefits, limitations and weakness of using this approach. The paper consists: I. Initiation, II. Outset of an approach, III. AHP-Axioms, IV.AHP - Algorithm, V. Enactments employing AHP, VI. Strengths, VII. Limitations, VIII. Weaknesses, IX. Variants of AHP, X. Criticisms, XI. Conclusions, XII. References